Pendampingan Sertifikasi Halal Pada Pelaku Usaha Mikro Kecil dan Menengah di Lombok - Efendi, Muhamad Zaki; Kusaeri, Al (State Islamic University of Mataram, 2024)
This volunteer project aims to educate business owners in Kembang Kerang Daya Village about the value of halal certification and provide support to micro, small, and medium-sized enterprises so that they can more easily issue halal certificates to their customers. The creation of halal labels is meant to boost the competitiveness of goods made by SMEs by allowing them to advertise themselves to a wider audience. Community-based participatory action research, including the description of available resources to potential collaborators, is the strategy used to put into action community service initiatives. In this activity, the resource person played a crucial role in explaining materials regarding halal labeling and how to expand marketing with the existence of a halal label on micro, small, and micro enterprise products during a meeting or face-to-face meeting between the resource person and partners in Kembang Kerang Daya Village. medium. Business Identification Numbers and Halal Certificates for Micro, Small, and Medium-Sized Business Products were the fruits of the community service activities that were put into action. Having a product certified as Halal may boost consumer trust, expand your customer base, and make your company more competitive.